2018
DOI: 10.1021/acs.energyfuels.8b03255
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features and Pyrolysis Behaviors of Extracts from Microwave-Assisted Extraction of a Low-Rank Coal with Different Solvents

Abstract: Microwave-assisted extraction (MAE) of a low-rank Naomaohu (NMH) coal was conducted with two solvents, cyclohexanone (CYC) and tetrahydrofuran (THF), to obtain extracts (ECYC and ETHF) and residues (RCYC and RTHF). The parent coal, extract, and residue were characterized by ultimate analysis, TG, FTIR, GPC, 1H NMR, and solid-state 13C NMR. The results showed that MAE process is more efficient than Soxhlet extraction. The solvent CYC exhibits a higher total extract yield of 8.3 wt % than THF, being 4.7 wt %, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In the zones of 3000–3600 cm –1 , there was a relatively wide and mild absorption peak, which was mainly categorized as various types of hydroxyl or hydrogen bonds. The spectrum was further analyzed and fitted piecewise, and functional groups corresponding to each peak were classified. , …”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the zones of 3000–3600 cm –1 , there was a relatively wide and mild absorption peak, which was mainly categorized as various types of hydroxyl or hydrogen bonds. The spectrum was further analyzed and fitted piecewise, and functional groups corresponding to each peak were classified. , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The spectrum was further analyzed and fitted piecewise, and functional groups corresponding to each peak were classified. 33,34 2.2.1. Analysis of Oxygen-Containing Absorption Band.…”
Section: Methodsmentioning
confidence: 99%
“…Using the MAE method with CYC as the solvent, the extract yield can reach 8.0 wt % (the formula of the extraction rate is given in the Supporting Information ), which is higher than that of other solvents, and 1 h for NMH coal. 28 E CYC accounts for about 8.7 wt % of coal organic matter. The mass spectrum of LIAD-VUVPI-TOFMS of E CYC is shown in Figure 4 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…They found that the solvent− solute interactions significantly influenced the extraction with tetrahydrofuran and ethyl acetate. Xiong et al 24 compared the pyrolysis of coals, their Rs, and extracts. They found that the significant mass loss (ML) of the Rs at temperatures slightly higher than 200 °C could be ascribed to the release of the extracts by thermal degradation.…”
Section: Introductionmentioning
confidence: 99%